SPIRITUALITAS KEKRISTENAN GEN Z: Perubahan Pola Penghayatan Iman Pada Generasi Digital - Tini Sarlota; Sambo Puang (ADISAM PUBLISHER, 2026)
Generation Z, born in the digital era, has experienced significant changes in the way they live out their Christian faith. This study aims to explore how Christian spirituality has developed among Gen Z, particularly in the digital context. Through a qualitative approach, this research analyzes the impact of technology and social media on their faith practices, as well as how this generation interacts with religious teachings through digital platforms. The findings suggest that Gen Z tends to seek more personal, flexible, and globally connected spiritual experiences. However, they still maintain core Christian values, albeit in a more fragmented and adaptive form in response to technological advancements. This study recommends the need for a more relevant and contextual approach in guiding Gen Z’s spirituality in the digital world.